SOME ASPECTS OF BIOLOGY OF Synodontis schall IN OYAN LAKE, SOUTH WESTERN NIGERIA - ODULATE, D. O; ATOBAALE, O. Y; AJAGBE, S. O; OJELADE, C. O; ABDUL, W. O; NWEKOYO, V. E; OPELE, A. I. (Nigerian Journal of Fisheries, 2023)
This study was carried out on natural diets and morphometric characteristics of Synodontis schall from Oyan Lake, Ogun State, Nigeria. A total of 150 fresh specimens of S. schall comprising 111 males and 39 females were collected on a monthly basis between February and August, 2017. The samples were preserved in ice-chest and transported to the laboratory where morphometric and meristic features were examined. Determination of sex and gut content analyses were also carried out. Frequency of occurrence and numerical method were used for gut content analysis. Descriptive statistics and correlations were employed to depict the results. Length-weight relationship was analyzed using regression analysis. Results revealed that the condition factor of male, female and combined sexes of S. schall were 1.010, 1.000 and 1.000 respectively. The study revealed that male specimens of S. schall exhibited negative allometric growth pattern with “b” value = 2.83. While, female and combined sexes (3.00 and 2.90 respectively) exhibited isometric growth pattern with regression values not significantly different (p>0.05) from 3. The highest positive correlation (0.99) was detected in standard length/fork length while, the least positive correlation (1.19) was detected in snout length/depth of caudal peduncle. A total of 68 organisms were identified as food items consumed by this species. Frequency of occurrence showed that Closterium (54.00%) was most consumed organism while numerically it was Nitzschia (6.95%). This species exhibited omnivorous feeding habit. The ratio of male to female was (2.9:1) respectively. It was concluded that Oyan Lake supported the thriving fisheries of the species where it showed a preponderance due to availability of a wider variety of dietary items. There should be reduction of fishing intensity during the peak spawning period of the fish stock.